A probe into the Filipino migration culture: What is there to learn for policy intervention? - Aubrey D. Tabuga (Philippine Institute for Development Studies (PIDS), 2018)
For many migrant workers, labor migration is not just a one-time, temporary means of livelihood, it has become the way of life. Among the 1.4 million land-based migrants in 2015, two-thirds comprise of re-hires. The number of new hires has been increasing as well. In fact, the trend of migrant deployment shows a continuous upward trend except during periods of crises and tight government control. From a public policy standpoint, this requires constant vigilance and informed decisionmaking with regard to designing policies and programs that look after the welfare of migrant workers. Some argue that while the government administers the deployment and implement strategies to promote the welfare of migrant workers, it also needs to design a more comprehensive long-term thrust for labor migration. The non-negligible number of cases of abuse, maltreatment, and crimes committed against Filipino migrant workers calls for a more defined policy that is less dependent on labor migration and more toward developing local job opportunities. This paper provides a deeper understanding of the migration motivations and intentions of Filipinos. Get a closer look at the migration intentions of individuals from a high-emigration rural village in the Philippines and some policy recommendations to address migration issues in this paper.
Keywords: 330; labor migration; migration intentions; networks in migration; Philippines; migration-related survey data